INTEGRASI, SCADA, DIGSILENT POWERFACTORY, OPC, STATE ESTIMATION. - Mushthofa Musyasy, Muhammad
This thesis research discusses the integration between Supervisory Control and Data Acquisition (SCADA) with DIgSILENT PowerFactory. This integration brings many benefits due to near real-time data transfer and can use the features of DIgSILENT PowerFactory for further analysis. The software used in this thesis research is DIgSILENT PowerFactory, MatrikonOPC Server for Simulation, MatrikonOPC Explorer, Microsoft Excel, Microsoft SQL Server, and Git. Meanwhile, the programming languages used are DIgSILENT Programming Language (DPL), Python, and SQL. The communication protocol used is OPC with the server using MatrikonOPC Server for Simulation and the clients are DIgSILENT PowerFactory and MatrikonOPC Explorer. The DIgSILENT PowerFactory features that will be used in this research are state estimation (SE), contingency analysis, and power flow analysis. SE input data come from the results of load flow analysis, with three datasets, peak load, base load, and peak load during working hours, with seven variations. The results obtained are the greater the variation of the error given, the greater the difference between the SE results and the results of the analysis of power flow and its deviation. In addition, the IISEA obtained always increases when the variation of the given error is also greater, except for the variation of the seventh data, which is between the variation of the second data and the variation of the third data or between the variation of the fifth data and the variation of the sixth data. The algorithm features contingency analysis, power flow analysis, retrieve historical data, and periodic also runs very well. The SE process takes 31 seconds, contingency analysis takes 12 seconds, load flow analysis takes 1 second, and historical data analysis takes 53 seconds.